Rational design of covalently bridged [FeIII 2M IIO] clusters - Alborés, Pablo (2010)
We are reporting the first supramolecular dimeric units of basic carboxylates. The neutral [FeIII 2MIIO] motif for different 3d M metals is covalently bound through 2,2′-bipyrimidine. We have structurally characterized the hexanuclear clusters and the related trinuclear building blocks. Their magnetic properties have been fully analyzed and DFT calculations have been performed as a supplementary tool. All results evidence a weak antiferromagnetic interaction through the bpym bridge between isolated spin ground states (in some examples) arising from intra-Fe 2MO core exchange couplings.